Preventing Breakdowns in Communication: Teaching Patient-Centered Posthospital Care Transitions to Medical Students - Maureen D. Lyons; D. Bailey Miles; Andrew M. Davis; Mark B. Saathoff; Amber T. Pincavage (Association of American Medical Colleges, 2016)
Abstract Introduction Patient-centered discharge care is critical to teach in clerkships: Studies have shown that patient-centered discharge care may reduce rehospitalization rates as well as ensure patient understanding after discharge. While these skills are necessary to be a successful intern, this is infrequently taught formally in clerkships. This session introduces medical students to challenges patients and providers face during care transitions, specifically, the transition after discharge from an inpatient hospital stay. Methods This workshop experience fosters the use of best communication-skills practices and team collaboration in discharge education and planning through reflective observation and role-play. Learners first identify common challenges faced when providing effective care transitions and then identify solutions to encourage patient-centered discharge care practices. Students also have the opportunity to be directly observed providing discharge care and to receive feedback using an observation tool. The materials associated with this publication include guidelines for workshop facilitators, blank video worksheet, completed video worksheet, teaching video, role-play exercise instructions and answer sheet for facilitators, direct observation tool, and workshop evaluation form. Results The majority of students agreed the workshop would be helpful in practicing effective discharge education (69/75, 92%) and in providing patient-centered care during care transitions (72/75, 96%). Observers and students using the discharge education card reported an average score of 4.3 out of 5 that the observation was a helpful educational experience, and 84% of the completed discharge education tools included comments on areas of improvement or an action plan. Discussion The tool is brief and user friendly, allowing for this exercise to be completed without difficulty during busy ward days. It also can be completed by residents or attendings depending on time constraints.